A Critical Evaluation of Educational Psychology - Mohammad Hadi Mahmoodi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Criticism is judging the merits and demerits of something and showing its weaknesses and strengths. Textbook evaluation, as a small step in learning and teaching process, can help teachers and learners find books that suit their needs and likes. In the present article, the book ‘Educational Psychology’ (the 13th global edition) authored by Anita Woolfolk (2016) is reviewed and evaluated.  This is a qualitative evaluation based on the writer’s experience in teaching this source in postgraduate classes for several years. To do so, the formal characteristics and the content of the book and the degree of its success in fulfilling the objectives, which are mentioned in the introduction of the book, are examined. Although this book, like any other book, is not flawless, it can surely be recommended to those who are interested in the learning-teaching process. It is hoped that, via this article, this book would be read and used by more people in the scientific community of Iran.